The invasion of the biliary epithelial cells by CD103+ CD69+ intraepithelial cells CD8+ T lymphocyte and its role in the pathogenesis of primary biliary cholangitis. (March 2023) - Ronca, V.; Davies, S.; Wootton, G.; Krajewska, N.; Reynolds, G.; Oo, Y.
Abstract : Introduction: The pathogenesis of primary biliary cholangitis (PBC) remains elusive and the mechanism of the biliary injury is yet to be clarified. Cell-in-cell structures (CICs) formed from lymphocytes have been reported in the liver. These are predominantly found within hepatocytes and have been associated with autoimmunity. Aims: We report for the first time the internalisation of CD8 + T cells in biliary epithelial cells in PBC. Our aim is to characterise the mechanism of the internalisation and explore its role in the pathogenesis of PBC. Materials and Methods Results: Immunofluorescence staining was used to identify and characterise CD8 + T cells internalised by BECs. Primary T cells were co-cultured with human BECs in vitro to assess the mechanism of internalisation. Morphology of co-cultured T cells and epithelial cells was visualised using confocal and electron microscopy, high-content imaging and flow cytometry. Internalised CD8 + T cells were found with higher frequency in PBC patients compared with diseased liver tissue. They were found to express CD103 + CD69 + and being significantly larger than liver parenchymal CD8 + T cells. Cells stimulation significantly increase their ability to invade BECs in vitro . Furthermore, the increased exposure to activation stimuli positively correlated with cell size and frequency of internalisation. Transmission electron microscopy confirmed complete internalisation in vitro and showed the lack of an additional membrane containing the T cell. Scanning electron microscopy revealed the polarisation of T cells prior to their internalisation and the absence of BEC membrane rearrangements associated with capture processes. These behaviours were not observed with matched CD4 + T cells. Conclusions: We described and characterised a population of hyper-activated CD8 + T Intraepithelial lymphocytes (IELs) which can invade cholangiocytes in patients with PBC. We reported for the first time the mechanism of this CiC process, demonstrating a novel ability of IELs to invade epithelial cells.